Examining the Factors of Organizational Citizenship Behaviour with reference to Corporate Sectors in Sultanate of Oman - Muthuraman, Subrahmanian; Al-Haziazi, Mohammed (International Review of Management and Marketing, 2017)
The study aimed to analyze the factors of organizational citizenship behavior in Sultanate of Oman. The employees in corporate sectors in Oman are expected to be highly effective and efficient in terms of commitment, productivity and performance. So the purpose of the study is to determine the extent to which employee’s exhibit the organizational citizenship behavior. Data was collected through a questionnaire by using likert scale for all the factors such as altruism, conscientiousness, civic virtue, sportsmanship and courtesy. The study was conducted by collecting 91 samples from various corporate sectors in Muscat city. Data has been analyzed by using multiple regressions, correlation, chi square and weighted average. Research findings indicate that all the factors were having a significant association with OCB. Analysis results reveal that four factors are the better predictor of OCB. The results also prove that there is a positive relationship between the factors and the OCB. Keywords: Organizational Citizenship behavior, altruism, conscientiousness, civic virtue, sportsmanship and courtesy JEL Classifications: L2, M1